DYE JET VELOCITY DISTRIBUTION MEASUREMENTS USING PHOTOTHERMAL DEFLECTION SPECTROSCOPY (Journal of Sciences, Islamic Republic of Iran)
We demonstrate that photothermal deflection spectroscopy can be used to measure velocity distributions in dye jets. Such measurements are useful in determining the quality of flow in dye jets, The quality of jets is very important for a stable and naanow linewidth operation of dye lasers